A Short Line Segment Squirms Along a Zigzag Line. (April 2013) - Ito, Hiroyuki; Yang, Xie
When a short straight line segment moves across a zigzag line and is viewed in one's peripheral vision, it appears to exhibit nonrigid squirming motion (the squirm effect). This phenomenon demonstrates that the form, orientation, and motion direction of a short line are influenced by those of a longer one when they are viewed in one's peripheral vision.